Influence of water activity on seed mycoflora of fennel - S.M. REDDY, D. RAJA KUMARI and (Indian Phytopathology, 2002)
Influence of water activity (aw) on the seed mycoflora of fennel tFoeniculum vulgare) seeds was investigated. At low aw, only a few xerophills like species of Aspergillus and Penicillium were present on the seed surface. Similarly at high aw again, a few fungi like Aspergillus flavus and A. nig er were dominant probably because of their competitive ability.